A comparison of the spatial patterns of β-amyloid (Aβ) deposits in five neurodegenerative disorders - A. Armstrong, Richard (Folia Neuropathologica, 2018)
Alzheimer’s disease neuropathologic change (ADNC) in the form of -amyloid (A) deposits is important not only in the pathogenesis of Alzheimer’s disease (AD) and Down’s syndrome (DS) but also as a ‘co-pathology’ in disorders such as dementia with Lewy bodies (DLB), corticobasal degeneration (CBD), and chronic traumatic encephalopathy (CTE). To compare cortical and hippocampal degeneration in different disorders, the spatial patterns of the diffuse, primitive, and classic A deposits were studied in regions of frontal and temporal cortex in five neurodegenerative disorders, viz. AD, DS, DLB, CBD, and CTE using spatial pattern analysis. In all disorders, the A deposits were clustered and in a proportion of brain regions, the clusters were regularly distributed parallel to the tissue boundary. Cluster dimensions in the cortex, measured parallel to the pia mater, were frequently in the range 400-800 m suggesting a spatial association with the cortico-cortical pathways. Differences were also observed among disorders, the diffuse A deposits being more frequently distributed in regular clusters in AD while cluster sizes of the diffuse and primitive deposits were significantly smaller in CTE. The data suggest considerable similarities in the spatial patterns of A deposits in different disorders, regardless of the clinical or pathological setting, which suggests that the spread of A via neuro-anatomical pathways may be common to several disorders.